Optimalisasi Sertifikasi Kesehatan Hewan untuk Karantina Produk Hewan di Kota Batam - Agustini, Shenti; Rusdiana, Shelvi; Sitompul, Grace Margareth Petricia (JUNCTO: Jurnal Ilmiah Hukum, 2023)
This study delves into the pivotal role of animal health certification in overseeing animal quarantine in Batam City and its profound impact on the local animal product industry. Positioned as Indonesia's economic and industrial hub, Batam City has witnessed rapid growth in the animal product sector. Animal health certification significantly contributes to upholding the quality and safety of animal products in the region, addressing not only regulatory compliance but also considerations for environmental sustainability, human health, consumer trust, and adherence to regulations like Law Number 18 of 2009 regarding Livestock and Animal Health. The research aims to elucidate the urgency and relevance of animal health certification, pinpoint relevant regulations, and expound on the implications of certification within the contexts of animal health, consumer safety, and the trade of animal products in Batam City. The ramifications of animal health certification in Batam City are highly noteworthy, fostering heightened consumer confidence in animal products. Employing the normative legal research method with literature as the primary approach, the findings reveal administrative challenges and logistical hurdles in implementing animal health certification, proposing improvement measures for system efficiency to support the overarching goals of animal health, food safety, and community well-being.